2003
DOI: 10.1046/j.1523-1739.2003.01265.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Agricultural Succession in El Petén, Guatemala

Abstract: We compared post-agricultural succession across the range of farming activities practiced in Guatemala's northern lowlands: agroforestry, swidden, ranching, and input-intensive monocultures. At 10 sites over 13 to 40 months we assessed the following characteristics of trees and shrubs that were Ͼ 1 cm diameter at breast height: height, basal-area accumulation, recruitment of all individuals and fleshy-fruited individuals, and accumulation of all species and fleshy-fruited species. Succession, as measured by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 47 publications
1
44
1
8
Order By: Relevance
“…Email: michiel.vanbreugel@wur.nl et al 2003, Finegan 1996. Explaining variation in successional pathways has been another major concern of studies of secondary forest, and important advances in linking such variation with environmental heterogeneity and land-use history has been made (Aide et al 1996, Chinea & Helmer 2003, Ferguson et al 2003, Mesquita et al 2001, Purata 1986.…”
Section: Introductionmentioning
confidence: 99%
“…Email: michiel.vanbreugel@wur.nl et al 2003, Finegan 1996. Explaining variation in successional pathways has been another major concern of studies of secondary forest, and important advances in linking such variation with environmental heterogeneity and land-use history has been made (Aide et al 1996, Chinea & Helmer 2003, Ferguson et al 2003, Mesquita et al 2001, Purata 1986.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, individuals that settle in secondary forest, experience microclimatic conditions (such as light availability, water availability, temperature, etc.) that are distinct from those found in mature forest, because the removal of the plant cover, alters the local microclimate and, additionally, the influence of biotic and abiotic factors becomes of higher intensity, when compared to the one that occurs in preserved habitats (Crozier, & Boerner, 1984;Ferguson et al, 2003;Tews et al, 2006;Andrade et al, 2007;Kostrakiewicz, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…During the first year after the earthquake, the seeds sprout quickly from the soil, and the dominate species are herbaceous plants. Other previous studies suggested that the presence of remnant vegetation is a driving factor for forest recovery [53,54]. Furthermore, Liu et al [36] found that local vegetation productivity in heavily affected areas had recovered to 84% and 87% after one and two months, respectively.…”
Section: Vegetation Recovery In the Earthquake Triggered Hazard Areasmentioning
confidence: 98%